Logics of worlds : being and event, 2 - Badiou, Alain (Continuum, 2009)
Logics of Worlds is the long-awaited sequel to Alain Badiou's much-heralded masterpiece, Being and Event. Tackling the questions that had been left open by Being and Event, and answering many of his critics in the process, Badiou supplements his pioneering treatment of multiple being with a daring and complex theory of the worlds in which truths and subjects make their mark - what he calls a materialist dialectic. The radical recasting of ontology in Being and Event is followed and complemented here by a thoroughgoing transformation in our very understanding of logic, conceived as a theory not of being but of appearing. Unafraid to resurrect and reinvent the classical themes of philosophy, Badiou gives new meaning to concepts such as object, body and relation, mobilising them in arresting studies that range from the architectural planning of Brasilia to contemporary astronomy, and confronting himself with towering philosophical counterparts (Leibniz, Kant, Hegel, Kierkegaard, Lacan, Deleuze). The book culminates in an impassioned call to 'live for an Idea'.